The Efforts in Law Enforcement for Personal Data Protection - Lumban Raja, Muhammad Dewo; Lie, Gunardi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The concept of the rule of law is crucial for the proper functioning of any state, ensuring that governance operates within the framework of legal regulations. This principle, outlined in Hans Nawiasky’s Theory of Legal Norm Hierarchy, prevents the abuse of power and guarantees that authority is exercised under legal oversight. Key features of the rule of law, such as legal certainty, equality before the law, and human rights protection, contribute to the creation of a just society. In the context of Indonesia, which is a constitutional state as per Article 1(3) of the 1945 Constitution, legal provisions such as the Personal Data Protection Law (UU PDP) are introduced to protect citizens' personal data, particularly within the rapidly growing digital financial services sector. Indonesia’s advancement into Industry 4.0 and the rise of financial technology (FinTech) have made data protection more urgent, especially in a digital economy where data sharing occurs across borders. The government’s legal response includes laws and regulatory frameworks that aim to safeguard users’ personal data while addressing challenges like low digital literacy, weak compliance, and cross-border data flows. This paper explores the implementation of these laws, examines the challenges in enforcing them, and proposes improvements for ensuring effective protection of personal data in Indonesia’s digital financial services.